Subjective Characteristics of the Criminal Legal Provisions of the Ruska Pravda - Колос, М. І. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article provides dogmatic analysis of subjective characteristics of the criminal legal provisions of the Ruska Pravda; the conclusion is made regarding common legal fundamentals of these provisions and those of modern national criminal law, which permanently provide the quality of law-making and law-enforcement at different stages of development of the Ukrainian statehood.